Every Breath You Take - McNaught, Judith (London Piatkus, 2005)
On the eve of wealthy philanthropist Cecil Wyatt's eightieth birthday, all the money in the world won't bring back his missing grandson, William Wyatt. The family, the police, and the media, have tried in vain to discover the young man's fate. Now, suspicion has turned shockingly toward William's own half-brother, the enigmatic Mitchell Wyatt.
Keywords: Man-Woman Relationships -- Murder--Investigation -- Rich People